VARIABEL YANG BERKONTRIBUSI PADA KEJADIAN PREEKLAMSIA BERAT PADA IBU HAMIL - Siti Hikmah; Ayudita; Siti Patimah (Jurnal Ilmiah Citra Kebidanan, 2025)
Preeclampsia is a disease with signs of hypertension, proteinuria, and edema that arise due to pregnancy and generally occurs in the third trimester or earlier. According to the World Health Organization (WHO), in 2021, an estimated 934 cases of preeclampsia occurred worldwide every day. Preeclampsia is included in the three main causes of complications during pregnancy and childbirth, the first is bleeding (30%), preeclampsia/eclampsia (25%), and infection (12%). The purpose of this study was to determine the factors associated with the incidence of severe preeclampsia at Bakti Timah Hospital, Pangkalpinang in 2022-2023. This study used a case-control study design. The population in this study were 560 pregnant women at RSBT in 2022-2023, with a sample of 122 divided into 61 case samples and 61 control samples. The case group in this study were pregnant women with severe preeclampsia, and the control group in this study were pregnant women who did not have severe preeclampsia. This study was conducted in August 2024. Data analysis used the Chisquare Test. The results of the analysis showed a significant relationship between maternal age with p-value = 0.000 OR = 4.406, parity with p-value = 0.001 OR = 4.050, History of PEB with p-value = 0.002 OR = 3.542 and obesity with p-value = 0.000 OR = 5.142 with the incidence of severe preeclampsia. The conclusion of this study is that there is a relationship between age, parity, history of PEB and obesity with the incidence of severe preeclampsia.